MICRONIZED CONCRETE POWDER AS MIRCOFILLER IN CEMENT PASTE: INFLUENCE ON HYDRATION AND STRUCTURE - Jaroslav Topič; Zdeněk Prošek (Acta Polytechnica CTU Proceedings, 2021)
The reuse of old concrete as a coarse and fine recycled aggregate in cement composites is relatively well researched, and therefore a very fine fraction of recycled concrete was used in this paper. When using a very fine fraction of recycled concrete, it is appropriate to focus primarily on less technologically demanding treatment processes with minimal costs and environmental impact. Therefore this paper focus on using the fine fraction of recycled concrete as a microfiller. For this purpose, the material is treated by high-speed milling process and micronized concrete powder (MCP) is produced. Using several micronized concrete powder types that differ by origin, separation process and fineness of grinding should help understand how MCP influences the hydration process and cement paste structure. The samples with 0, 10, 20, 30, 40 and 50 wt. % of MCP were made to determine proper dosage in cement paste. Specific surface, matrix density and DTG analysis of micronized concrete powder were carried out. The calorimetric measurement was used to confirm how microfiller affects the hydration process. Finally, bulk density and porosity measurements were performed to determine the effect of MCP and its amount on the cement paste structure.